Approaching an Auschwitz survivor : Holocaust testimony and its transformations - Matthäus, Jürgen 1959- (Oxford Univ. Pr, 2009)
"Five Holocaust scholars reflect on the testimony of one survivor, Helen "Zippi" Tichauer and watch her testimony--and scholarly responses to it--evolve over the years"--Provided by publisher